Implementasi Paket Bantuan Sosial Sebagai Upaya Menghadapi Pandemi Covid-19 - Aldi Budi Riyanta; Heru Nurcahyo; Joko Santoso (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2020)
Global pandemic has a significant effect of decreasing economic activity. This certainly has an impact on the ability of the community to meet their daily needs. The low-cost staple program is felt to be lacking in low-income and poor communities and the role of educational institutions is expected to be able to overcome this with an aid package program. The aim of this community service is to target the community of daily wages by providing direct assistance packages such as groceries, hand sanitizers, masks and some money. This activity gave a very good response from the people who were given assistance with the distribution of this basic food package model. The activity was also added with covid-19 prevention education in general with the hope of helping to increase the productivity of the grassroots in breaking the chain of distribution of covid-19. The results of this activity went well with the distribution of all aid packages to the target community was given covid-19 prevention education to increase knowledge in order to break the chain of distribution of covid-19.